Extensive genetic diversity of severe fever with thrombocytopenia syndrome virus circulating in Hubei Province, China, 2018-2022. - Yu-Ting Ren; Hong-Pan Tian; Jia-le Xu; Man-Qing Liu; Kun Cai; Shu-Liang Chen; Xue-Bing Ni; Yi-Rong Li; Wei Hou; Liang-Jun Chen (Public Library of Science (PLoS), 2023)
Severe fever with thrombocytopenia syndrome virus (SFTSV), an etiological agent causing febrile human disease was identified as an emerging tick-borne bunyavirus. The clinical disease characteristics and case fatality rates of SFTSV may vary across distinct regions and among different variant genotypes. From 2018 to 2022, we surveyed and recruited 202 severe fever with thrombocytopenia syndrome (SFTS) patients in Hubei Province, a high-incidence area of the epidemic, and conducted timely and systematic research on the disease characteristics, SFTSV diversity, and the correlation between virus genome variation and clinical diseases. Our study identified at least 6 genotypes of SFTSV prevalent in Hubei Province based on the analysis of the S, M, and L genome sequences of 88 virus strains. Strikingly, the dominant genotype of SFTSV was found to change during the years, indicating a dynamic shift in viral genetic diversity in the region. Phylogenetic analysis revealed the genetic exchange of Hubei SFTSV strains was relatively frequent, including 3 reassortment strains and 8 recombination strains. Despite the limited sample size, SFTSV C1 genotype may be associated with higher mortality compared to the other four genotypes, and the serum amyloid A (SAA) level, an inflammatory biomarker, was significantly elevated in these patients. Overall, our data summarize the disease characteristics of SFTSV in Hubei Province, highlight the profound changes in viral genetic diversity, and indicate the need for in-depth monitoring and exploration of the relationship between viral mutations and disease severity.